A Rare Case of Multiple Hereditary Exostosis: Making The Correct Diagnosis with Triple Diagnosis - Rahmi Ramadhani; Noza Hilbertina; Yenita; Tofrizal; Pamelia Mayorita; Loli Devianti; Meta Zulyati O ktora (Scientific Journal, 2025)
Background: A rare genetic disorder characterized by the development of multiple benign bone tumors called osteochondromas. This condition is primarily hereditary and follows an autosomal dominant pattern of inheritance, with mutations in the EXT1 and EXT2 genes being the most common genetic. Case report: This case report describes an 12-year-old boy with lumps in all four extremities accompanied by intermittent pain. Femur x-rays concluded MHE of the femur, tibia, and bilateral fibula. Histopathological examination shows that the cartilage tissue contains chondrocyte cells that form the cartilage cap. There is a transition of cartilage to bone trabeculae through endochondral ossification and bone marrow between the bone trabeculae. Discussion and Conclusion: MHE is a rare condition, with an incidence of approximately 1 in 50,000 to 100,000 live births. MHE is closely related to genetic mutations that occur in the EXT1, EXT2, and EXT3 genes. These genes code for enzymes involved in the biosynthesis of heparan sulfate, which is necessary for normal bone growth. Mutations in any of these genes disrupt the regulation of bone growth and lead to osteochondroma formation. Symptoms of MHE can range from mild to severe, and they tend to appear in childhood or adolescence. The main clinical manifestations include the formation of a hard lump on the bone, which can cause deformity, pain, and limitation of movement. Osteochondroma can also compress nerves or blood vessels, causing complications such as circulatory disorders or paralysis. We report a rare case emphasizing the typical morphology of multiple hereditary exostosis of the long bones to establish the final diagnosis without immunohistochemistry and molecular examination. In low-resource settings where molecular analysis is not available, histopathological examination are key tools to establish a correct diagnosis.